2023
DOI: 10.1021/acs.jafc.3c02432
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Production of N-Acetylneuraminic Acid in Escherichia coli Based on the UDP-N-Acetylglucosamine Biosynthetic Pathway

Abstract: N-Acetylneuraminic acid (NeuAc) is the predominant sialic acid found in human cells and a human-identical milk monosaccharide. Due to its numerous health benefits, it has great commercial potential in the pharmaceutical, cosmetic, and food industries. Microbial synthesis via metabolic engineering strategies is an important approach to its large-scale production. In this study, a NeuAc synthetic pathway was constructed in Escherichia coli BL21(DE3) by deleting the competitive pathway genes and introducing two g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Translational impact for sialic acids faces a number of challenges going forwards. While the scalable enzymatic synthesis of sialic acid [155][156][157][158] and sialylated glycans [159][160][161] has been achieved, the correct presentation of this key sugar recognition element is critical to achieving physiologically or therapeutically relevant biological recognition. For instance, the valency of NeuAc presentation 97 as well as secondary interactions from the glycan chain to which it is attached 140 can have a profound impact on target engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Translational impact for sialic acids faces a number of challenges going forwards. While the scalable enzymatic synthesis of sialic acid [155][156][157][158] and sialylated glycans [159][160][161] has been achieved, the correct presentation of this key sugar recognition element is critical to achieving physiologically or therapeutically relevant biological recognition. For instance, the valency of NeuAc presentation 97 as well as secondary interactions from the glycan chain to which it is attached 140 can have a profound impact on target engagement.…”
Section: Discussionmentioning
confidence: 99%
“…To alleviate this metabolic burden, we propose to further optimize gene expression levels through engineering promoters and ribosome-binding sites to better balance the protein expression, LLO production, and glycosylation processes. As improving the terminal sialylation efficiency remains a challenge and other studies have suggested that overexpression of neuA , to supplement CMP-Neu5Ac, and alkaline phosphatase can decrease the efficiency of the sialidase enzyme, thereby increasing its sialyltransferase efficiency ( Kang et al, 2015 ; Zhang et al, 2022 ; Zhao et al, 2023 ), we will focus on incorporating a stronger promoter into the neuBCA gene cluster, as well as screening other α-2,3-sialyltransferases to optimize sialylation.…”
Section: Discussionmentioning
confidence: 99%